SENSITIVITAS DOLLAR, YUAN, YEN DAN SBI TERHADAP IHSG - Umi Murtini; Cynthia Septivanie (Jurnal Riset Akuntansi dan Keuangan, 2016)
The purpose of this research is to test sensitivity of the Dollar exchange rate, Yuan exchange rate, Yenexchange rate, and interest rate to IHSG. The sample used in this studi are daily exchange rate from 1January 2015 to 30 September 2015 was got from daily report of Bank Indonesian, and then monthlyinterest rate was got from monthly report of Bank Indonesian. Hypothesis test used in this study isVector Error Correction Model (VECM). The result of this study indicate that IHSG to have sensitiveto USD variable, JPY variable, CNY variable, and SBI. IHSG have to sensitive negatif to variableCNY and SBI, while IHSG have to sensitive positive to USD and JPY .Keyword : Interest Rate, Dollar Exchange Rate, JPY, CNY, IHSG, ECM